2015
DOI: 10.1186/s13046-015-0160-7
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein increases the expression and reciprocal interplay of RUNX3 and FOXO3a through crosstalk of AMPKα and MEK/ERK1/2 signaling pathways in human non-small cell lung cancer cells

Abstract: BackgroundBaicalein, a natural flavonoid obtained from the Scutellaria baicalensis root, has been reported to inhibit growth of human lung cancer. However, the detailed mechanism underlying this has not been well elucidated.MethodsCell viability was measured using a 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assays. Apoptosis was detected by flow cytometry analysis and caspase 3/7 assays. The expression of RUNX3 and FOXO3a mRNA were measured by real time RT-PCR methods. Western blot a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 47 publications
(60 reference statements)
1
36
0
Order By: Relevance
“…Paradoxically, with the discoveries reported by Nevadunsky et al (13) and Lee et al (14), found that RUNX3 took on a growth-stimulating role, which was highly active in ovarian cancer cells, likewise, it even played an oncogenic role in basal cell carcinoma, head and neck squamous cell carcinoma (15,16). Moreover, reports have found that RUNX3 inactivation can be correlated with advanced tumor stage and negative prognosis (17), and acts as a crucial early step in the development of tumors (18,19). To date, our purpose is to preliminarily explore the expression and the biological behavior of RUNX3 in cervical cancer.…”
mentioning
confidence: 98%
“…Paradoxically, with the discoveries reported by Nevadunsky et al (13) and Lee et al (14), found that RUNX3 took on a growth-stimulating role, which was highly active in ovarian cancer cells, likewise, it even played an oncogenic role in basal cell carcinoma, head and neck squamous cell carcinoma (15,16). Moreover, reports have found that RUNX3 inactivation can be correlated with advanced tumor stage and negative prognosis (17), and acts as a crucial early step in the development of tumors (18,19). To date, our purpose is to preliminarily explore the expression and the biological behavior of RUNX3 in cervical cancer.…”
mentioning
confidence: 98%
“…Treatment with baicalein also inhibited lung carcinogenesis by counteracting lysosomal and microsomal abnormalities through the reduction of oxidative damages and downregulation of CYP1A1 [95]. Moreover, baicalein treatment inhibited proliferation and induced apoptosis of NSC lung cancer cells by phosphorylation of AMPKα and MEK/ERK1/2, and upregulating the expression of RUNX3 and FOXO3a [96]. Interestingly, baicalein effectively decreased the levels of TNF-α, IL-β, iNOS, COX-2, MMP-2, and MMP-9.…”
Section: Baicalein and Lung Cancermentioning
confidence: 99%
“…Numerous studies have demonstrated that FOXO3a regulated a wide range of biological functions including growth, differentiation, apoptosis, protection against oxidative stress, and metabolism [9-11]. Exogenously expression of FOXO3a has been shown to inhibit tumor growth in several cancer types [12, 13]. These observations suggest that FOXO3a functions as a tumor suppressor and may serve as a therapeutic target for the cancer treatment.…”
Section: Introductionmentioning
confidence: 99%